PERAN UNAIDS (THE JOINT UNITED NATIONS PROGRAMME ON HIV/AIDS) DALAM PENANGANAN HIV/AIDS DI ZIMBABWE - Febrina Khairi; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explains about how the UNAIDS role in handling HIV/AIDS in Zimbabwe. Zimbabwe is one of the poor country that have bad health issue. The issue of HIV/AIDS has become a problem in Zimbabwe. HIV/AIDS is a matter that attract attention in zimbabwe which can be seen from the high number of patients. Zimbabwe is also known for high poverty rates which causes higher mortality rates because of HIV/AIDS. The high HIV/AIDS mortality rates is caused by the inability to buy drugs. therefore, as the organization responsible for the problem of HIV/AIDS in the world, UNAIDS entered as foundation that give grant funds and health programs in Zimbabwe.This research theoretically has built with Pluralism perspectives on International Relations and supported by International Organization theories, and also the Role theories. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library.Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis which reveals the fact that role of UNAIDS as in the form of education, treatment, care, and support for patients in Zimbabwe. UNAIDS makes programs such as ABC (Abstain, Be Faithful, and Use Condom), harm reduction and PMTCT (Preventing Mother To Child transmition). The program has been spearheaded by all stakeholders that includes public and private sectors, NGOs, formal and informal institutions and intergovernmental organizations. With all the programs from UNAIDS, the HIV/AIDS threat can be reducted.Keyword : UNAIDS, Zimbabwe, HIV/AIDS, Role UNAIDS